2015
DOI: 10.3747/pdi.2013.00010
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Peritoneal Dialysis Fluids with Cell Cycle Mechanisms

Abstract: ♦ Introduction: Peritoneal dialysis fluids (PDF) differ with respect to osmotic and buffer compound, and pH and glucose degradation products (GDP) content. The impact on peritoneal membrane integrity is still insufficiently described. We assessed global genomic effects of PDF in primary human peritoneal mesothelial cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 72 publications
(76 reference statements)
0
22
0
Order By: Relevance
“…Whole exome expression analyses in human peritoneal mesothelial cells [ 9 ] demonstrated significant regulation of heme oxygenase-1 by PD fluids (p<0.000001) but of no other gene known to be involved in angiogenesis. In a separate set of experiments using new human peritoneal mesothelial cells lines from 4 different donors, quantification of heme oxygenase-1, angiopoietin-1, angiopoietin-2, VEGF-A, matrix metalloproteinase-1, fibroblast growth factor-2 and hypoxia-inducible factor-1a by qRT-PCR demonstrated no difference following LPDF and BPDF treatment, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole exome expression analyses in human peritoneal mesothelial cells [ 9 ] demonstrated significant regulation of heme oxygenase-1 by PD fluids (p<0.000001) but of no other gene known to be involved in angiogenesis. In a separate set of experiments using new human peritoneal mesothelial cells lines from 4 different donors, quantification of heme oxygenase-1, angiopoietin-1, angiopoietin-2, VEGF-A, matrix metalloproteinase-1, fibroblast growth factor-2 and hypoxia-inducible factor-1a by qRT-PCR demonstrated no difference following LPDF and BPDF treatment, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro , lactate exerts significant mesothelial cell toxicity, even at neutral pH [ 8 ]. Bicarbonate buffered PD fluid with low glucose degradation product content induces less mesothelial gene regulation [ 9 ], less oncosis [ 10 ] and up-regulates aquaporin-1 dependent mesothelial cell migration [ 11 ]. In rats, pH adjusted lactate fluid induces more mesenterial angiogenesis than the respective bicarbonate buffered fluid, independent of the presence of glucose [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gotloib et al reported a higher degree of oxidative injury to the peritoneum. Büchel et al showed that icodextrin reduces the activity of mesothelial cells.…”
Section: Discussionmentioning
confidence: 86%
“…They showed an increment of P16 expression and β‐gal staining in mesothelial cells after stimulation with conventional icodextrin PDF. Büchel et al analyzed the effects of several PDFs on peritoneal cell cycle genes, and they showed that conventional icodextrin PDF stimulated P21 mRNA expression. From these results, we considered that conventional icodextrin might have inhibitory effects on cell growth and lead to cell senescence in mesothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation